Preparation method of biomass porous carbonized material and porous carbonized material
Through ball milling improvement, gradient heat treatment and hot pressing treatment of biomass carbon, combined with the use of modified cycle stabilizers, porous carbonized materials with excellent adsorption and cycle stability were prepared, which solved the poor performance of existing porous carbon materials. The problem of this has achieved the improvement of efficient wastewater treatment and circulation performance.
Patent Information
- Application Number
- CN202310493916.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-05-05
AI Technical Summary
The existing porous carbonized materials have poor effects in circulation and adsorption properties, and are poor in stability, making them difficult to optimize.
Using biomass carbon as the base material, improved treatment, gradient heat treatment and hot pressing treatment through ball milling, combined with a modified cycle stabilizer, porous carbonized materials with excellent adsorption and cycle stability were prepared.
It significantly improves the adsorption efficiency and circulation performance of wastewater, improves the stability of discharge specific capacity and circulation discharge capacity, and enhances the circulation stability of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbonized materials, and in particular to a preparation method of a biomass porous carbonized material and the porous carbonized material. Background Art
[0002] With the rapid development of social economy and the rapid increase in population, people's demand for energy is increasing. However, due to the non-renewable nature of fossil energy such as oil, coal, and natural gas, after a long period of exploitation, they are gradually unable to meet the needs of economic and social development. In addition, the large amount of greenhouse gases and toxic gases produced by the combustion of fossil energy are also endangering our living environment. In recent years, with the improvement of people's environmental awareness, people's calls for clean energy are getting louder and louder, and the development of clean, efficient, and energy-saving new energy to replace fossil energy has become a hot topic for researchers.
[0003] Wastewater refers to the general term for water discharged during residents' activities and runoff rainwater. It includes domestic sewage, industrial wastewater, and other unused water such as initial rain runoff into drainage pipes. It generally refers to water that cannot be recycled after certain technical treatment or water that cannot meet certain standards for purification after primary pollution. It is also called sewage, which is water produced in a certain production and life process of human beings that has lost its use value or cannot be used. Wastewater discharged into the environment can cause water pollution. Porous carbon can be used as wastewater adsorption to improve wastewater treatment efficiency; in addition, porous carbon materials are often used as electrode materials in energy storage fields such as supercapacitors and lithium batteries.
[0004] Existing porous carbonized materials are mostly used for adsorption and wastewater adsorption, but have poor effects on circulation performance, cannot achieve high retention rate of circulation performance, and have poor performance stability. The optimization and coordinated improvement of adsorption and circulation performance is the technical point of the present invention. Based on this, the present invention further improves and processes it. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing a porous carbonized biomass material and a porous carbonized biomass material to solve the problems raised in the above background technology.
[0006] The present invention solves the technical problem by adopting the following technical solution:
[0007] The present invention provides a method for preparing a porous biomass carbonized material, comprising the following steps:
[0008] Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed;
[0009] Step 2: Then perform the first level of gradient heat treatment, the specific method is: first raise the temperature to 300-350°C, keep it warm for 5-10 minutes, and then cool it to room temperature with water;
[0010] Step 3: Place in 3-5 times the modified cycle stabilizer and stir for modification treatment, the stirring temperature is 40-50°C, the stirring time is 20-30min, the stirring speed is 300-400r / min, after the stirring is completed, wash with water and dry;
[0011] Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment;
[0012] The specific method is: first increase the temperature to 50-60°C at a rate of 1-3°C / s, keep warm for 1-5 minutes, then increase the temperature to 80-90°C at a rate of 2-5°C / s, keep warm for 2-5 minutes, and then air cool to room temperature;
[0013] Step 5: Finally, hot pressing is performed to obtain the porous carbonized material of the present invention.
[0014] Preferably, the biomass carbon is obtained by carbonizing rice husks in a carbonization furnace at a carbonization temperature of 650-700° C. for a carbonization time of 2-4 hours.
[0015] Preferably, the ball milling improvement treatment method is:
[0016] S01: pre-modify the bentonite, and then set it aside after the modification is completed;
[0017] S02: adding the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, and then adding 2-5% chitosan and 1-3% carboxymethyl cellulose based on the total amount of bentonite, stirring evenly to obtain a pre-modified bentonite composite conditioner;
[0018] S03: placing the flaky talc in a 3-5 times hydrochloric acid solution and stirring to disperse the flaky talc, stirring evenly to obtain a flaky talc agent;
[0019] S04: Add S03 flaky talc powder to 3-5 times of pre-modified bentonite composite conditioner and stir for reaction. After stirring, wash with water and dry to obtain bentonite composite ball mill;
[0020] S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, the mixture is ready.
[0021] Preferably, the pre-modification treatment step is: first react at a temperature of 350-400°C for 1-2h, and then cool to room temperature at a rate of 2-5°C / min.
[0022] Preferably, the mass fraction of the lanthanum sulfate solution is 10-20%, and the mass fraction of the hydrochloric acid solution is 2-5%.
[0023] Preferably, the temperature of the S04 stirring reaction is 45-55°C, the stirring time is 20-30min, and the stirring speed is 550-750r / min.
[0024] Preferably, the ball milling speed in S05 is 1000-1500 r / min, and the ball milling time is 20-30 min.
[0025] Preferably, the modified circulation stabilizer comprises the following raw materials in parts by weight:
[0026] 2-5 parts of nickel nitrate, 10-20 parts of deionized water, 1-4 parts of resorcinol, and 0.2-0.6 parts of silane coupling agent KH560.
[0027] Preferably, the pressure of the hot pressing treatment is 10-15 MPa, and the treatment time is 20-30 min.
[0028] The invention also provides a porous carbonized material prepared by a method for preparing a biomass porous carbonized material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The porous carbonized material of the present invention uses biomass carbon as a base material, is improved by ball milling, and is combined with a first-stage gradient heat treatment, a second-stage gradient heat treatment, and finally a hot pressing treatment. At the same time, the first-stage and second-stage heat treatments are stirred and modified in a modified cycle stabilizer. The prepared product has porous adsorption, and can improve the adsorption efficiency of wastewater when applied in wastewater. In terms of cycle performance, it has excellent discharge specific capacity and cycle discharge capacity stability.
[0031] In the ball milling improvement, bentonite is first pre-improved to increase its interlamellar spacing, and then it is compounded with raw materials such as lanthanum sulfate solution and mixed with flaky talcum powder. The flaky talcum powder is activated by hydrochloric acid solution and interspersed in the interlaminar spacing of bentonite. It is then improved by ball milling and mixed with the matrix raw materials. The prepared product has excellent cycle stability. The modified cycle stabilizer is mixed with nickel nitrate, resorcinol, and silane coupling agent KH560. After the modification process, the cycle stability of the optimized product is further improved. Implementation
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A method for preparing a porous biomass carbonized material according to this embodiment comprises the following steps:
[0034] Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed;
[0035] Step 2: Then perform the first level of gradient heat treatment, the specific method is: first raise the temperature to 300-350°C, keep it warm for 5-10 minutes, and then cool it to room temperature with water;
[0036] Step 3: Place in 3-5 times the modified cycle stabilizer and stir for modification treatment, the stirring temperature is 40-50°C, the stirring time is 20-30min, the stirring speed is 300-400r / min, after the stirring is completed, wash with water and dry;
[0037] Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment;
[0038] The specific method is: first increase the temperature to 50-60°C at a rate of 1-3°C / s, keep warm for 1-5 minutes, then increase the temperature to 80-90°C at a rate of 2-5°C / s, keep warm for 2-5 minutes, and then air cool to room temperature;
[0039] Step 5: Finally, hot pressing is performed to obtain the porous carbonized material of the present invention.
[0040] The biomass carbon of this embodiment is obtained by carbonizing rice husk in a carbonization furnace at a carbonization temperature of 650-700° C. for a carbonization time of 2-4 hours.
[0041] The method of ball milling improvement treatment in this embodiment is:
[0042] S01: pre-modify the bentonite, and then set it aside after the modification is completed;
[0043] S02: adding the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, and then adding 2-5% chitosan and 1-3% carboxymethyl cellulose based on the total amount of bentonite, stirring evenly to obtain a pre-modified bentonite composite conditioner;
[0044] S03: placing the flaky talc in a 3-5 times hydrochloric acid solution and stirring to disperse the flaky talc, stirring evenly to obtain a flaky talc agent;
[0045] S04: Add S03 flaky talc powder to 3-5 times of pre-modified bentonite composite conditioner and stir for reaction. After stirring, wash with water and dry to obtain bentonite composite ball mill;
[0046] S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, the mixture is ready.
[0047] The steps of the pre-modification treatment in this embodiment are: first react at a temperature of 350-400°C for 1-2h, and then cool to room temperature at a rate of 2-5°C / min.
[0048] The mass fraction of the lanthanum sulfate solution in this embodiment is 10-20%, and the mass fraction of the hydrochloric acid solution is 2-5%.
[0049] The temperature of the S04 stirring reaction in this embodiment is 45-55°C, the stirring time is 20-30min, and the stirring speed is 550-750r / min.
[0050] In S05 of this embodiment, the ball milling speed is 1000-1500 r / min, and the ball milling time is 20-30 min.
[0051] The modified circulation stabilizer of this embodiment includes the following raw materials in parts by weight:
[0052] 2-5 parts of nickel nitrate, 10-20 parts of deionized water, 1-4 parts of resorcinol, and 0.2-0.6 parts of silane coupling agent KH560.
[0053] The pressure of the hot pressing treatment in this embodiment is 10-15 MPa, and the treatment time is 20-30 min.
[0054] The porous carbonized material is prepared by a method for preparing a porous carbonized biomass material in this embodiment.
[0055] Example 1
[0056] The method for preparing the porous carbonized biomass material of this embodiment comprises the following steps:
[0057] Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed;
[0058] Step 2: Then, the first level of gradient heat treatment is performed. The specific method is: the temperature is first raised to 300°C, kept at this temperature for 5 minutes, and then cooled to room temperature by water cooling;
[0059] Step 3: Place in 3 times the modified cycle stabilizer and stir for modification treatment, the stirring temperature is 40°C, the stirring time is 20min, the stirring speed is 300r / min, after the stirring is completed, wash with water and dry;
[0060] Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment;
[0061] The specific method is: the temperature is first raised to 50°C at a rate of 1°C / s, kept at that temperature for 1 minute, then raised to 80°C at a rate of 2°C / s, kept at that temperature for 2 minutes, and then air-cooled to room temperature;
[0062] Step 5: Finally, hot pressing is performed to obtain the porous carbonized material of the present invention.
[0063] The biomass carbon in this embodiment is obtained by carbonizing rice husk in a carbonization furnace at a carbonization temperature of 650° C. for 2 hours.
[0064] The method of ball milling improvement treatment in this embodiment is:
[0065] S01: pre-modify the bentonite, and then set it aside after the modification is completed;
[0066] S02: Add the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, then add 2% chitosan and 1% carboxymethyl cellulose based on the total amount of bentonite, stir evenly, and obtain a pre-modified bentonite composite conditioner;
[0067] S03: placing the flaky talc powder in a 3-fold hydrochloric acid solution and stirring and dispersing the flaky talc powder, stirring the flaky talc powder evenly to obtain a flaky talc powder;
[0068] S04: Add S03 flaky talc powder to 3 times the pre-modified bentonite composite conditioner and stir for reaction. After stirring, wash with water and dry to obtain a bentonite composite ball mill.
[0069] S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, the mixture is ready.
[0070] The steps of the pre-modification treatment in this embodiment are: first react at a temperature of 350° C. for 1 hour, and then cool to room temperature at a rate of 2° C. / min.
[0071] The mass fraction of the lanthanum sulfate solution in this embodiment is 10%, and the mass fraction of the hydrochloric acid solution is 2%.
[0072] The temperature of the S04 stirring reaction in this embodiment is 45° C., the stirring time is 20 min, and the stirring speed is 550 r / min.
[0073] In S05 of this embodiment, the ball milling speed is 1000 r / min and the ball milling time is 20 min.
[0074] The modified circulation stabilizer of this embodiment includes the following raw materials in parts by weight:
[0075] 2 parts of nickel nitrate, 10 parts of deionized water, 1 part of resorcinol, and 0.2 parts of silane coupling agent KH560.
[0076] The pressure of the hot pressing treatment in this embodiment is 10 MPa, and the treatment time is 20 min.
[0077] The porous carbonized material is prepared by a method for preparing a porous carbonized biomass material in this embodiment.
[0078] Example 2
[0079] The method for preparing the porous carbonized biomass material in this embodiment includes the following steps:
[0080] Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed;
[0081] Step 2: Then, the first level of gradient heat treatment is performed, and the specific method is: the temperature is first raised to 350°C, kept at this temperature for 10 minutes, and then cooled to room temperature by water cooling;
[0082] Step 3: Place in 5 times the modified cycle stabilizer and stir for modification treatment, the stirring temperature is 50°C, the stirring time is 30min, the stirring speed is 400r / min, after the stirring is completed, wash with water and dry;
[0083] Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment;
[0084] The specific method is: the temperature is first raised to 60°C at a rate of 3°C / s, kept at this temperature for 5 minutes, then raised to 90°C at a rate of 5°C / s, kept at this temperature for 5 minutes, and then air-cooled to room temperature;
[0085] Step 5: Finally, hot pressing is performed to obtain the porous carbonized material of the present invention.
[0086] The biomass carbon in this embodiment is obtained by carbonizing rice husk in a carbonization furnace at a carbonization temperature of 700° C. for 4 hours.
[0087] The method of ball milling improvement treatment in this embodiment is:
[0088] S01: pre-modify the bentonite, and then set it aside after the modification is completed;
[0089] S02: Add the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, then add 5% chitosan and 3% carboxymethyl cellulose based on the total amount of bentonite, stir evenly, and obtain a pre-modified bentonite composite conditioner;
[0090] S03: placing the flaky talc powder in a 5-fold hydrochloric acid solution and stirring and dispersing the solution, stirring the solution evenly to obtain a flaky talc powder;
[0091] S04: S03 flaky talc is added to 5 times the pre-modified bentonite composite conditioner and stirred for reaction. After stirring, the mixture is washed with water and dried to obtain a bentonite composite ball mill;
[0092] S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, the mixture is ready.
[0093] The steps of the pre-modification treatment in this embodiment are: first react at a temperature of 400° C. for 2 hours, and then cool to room temperature at a rate of 5° C. / min.
[0094] The mass fraction of the lanthanum sulfate solution in this embodiment is 20%, and the mass fraction of the hydrochloric acid solution is 5%.
[0095] The temperature of the S04 stirring reaction in this embodiment is 55° C., the stirring time is 30 min, and the stirring speed is 750 r / min.
[0096] In S05 of this embodiment, the ball milling speed is 1500 r / min and the ball milling time is 30 min.
[0097] The modified circulation stabilizer of this embodiment includes the following raw materials in parts by weight:
[0098] 5 parts of nickel nitrate, 20 parts of deionized water, 4 parts of resorcinol, and 0.6 parts of silane coupling agent KH560.
[0099] The pressure of the hot pressing treatment in this embodiment is 15 MPa, and the treatment time is 30 min.
[0100] The porous carbonized material is prepared by a method for preparing a porous carbonized biomass material in this embodiment.
[0101] Example 3
[0102] The method for preparing the biomass porous carbonized material comprises the following steps:
[0103] Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed;
[0104] Step 2: Then, the first level of gradient heat treatment is performed, and the specific method is: the temperature is first raised to 325°C, kept at this temperature for 7.5 minutes, and then cooled to room temperature by water cooling;
[0105] Step 3: Place it in 4 times the modified circulating stabilizer and stir it for modification treatment. The stirring temperature is 45°C, the stirring time is 25min, and the stirring speed is 350r / min. After the stirring is completed, wash it with water and dry it;
[0106] Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment;
[0107] The specific method is: the temperature is first raised to 55°C at a rate of 2°C / s, kept at this temperature for 3 minutes, then raised to 86°C at a rate of 3°C / s, kept at this temperature for 3 minutes, and then air-cooled to room temperature;
[0108] Step 5: Finally, hot pressing is performed to obtain the porous carbonized material of the present invention.
[0109] The biomass carbon in this embodiment is obtained by carbonizing rice husk in a carbonization furnace at a carbonization temperature of 670° C. for 3 hours.
[0110] The method of ball milling improvement treatment in this embodiment is:
[0111] S01: pre-modify the bentonite, and then set it aside after the modification is completed;
[0112] S02: Add the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, then add 3.5% chitosan and 2% carboxymethyl cellulose based on the total amount of bentonite, stir evenly, and obtain a pre-modified bentonite composite conditioner;
[0113] S03: placing the flaky talc powder in a 4-fold hydrochloric acid solution and stirring and dispersing the solution, stirring the solution evenly to obtain a flaky talc powder;
[0114] S04: S03 flaky talc is added to 4 times the pre-modified bentonite composite conditioner and stirred for reaction. After stirring, the mixture is washed with water and dried to obtain a bentonite composite ball mill;
[0115] S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, the mixture is ready.
[0116] The steps of the pre-modification treatment in this embodiment are: first react at a temperature of 370° C. for 1.5 h, and then cool to room temperature at a rate of 3° C. / min.
[0117] The mass fraction of the lanthanum sulfate solution in this embodiment is 15%, and the mass fraction of the hydrochloric acid solution is 3%.
[0118] The temperature of the S04 stirring reaction in this embodiment is 50° C., the stirring time is 25 min, and the stirring speed is 600 r / min.
[0119] In S05 of this embodiment, the ball milling speed is 1250 r / min and the ball milling time is 25 min.
[0120] The modified circulation stabilizer of this embodiment includes the following raw materials in parts by weight:
[0121] 3.5 parts of nickel nitrate, 15 parts of deionized water, 2 parts of resorcinol, and 0.4 parts of silane coupling agent KH560.
[0122] The pressure of the hot pressing treatment in this embodiment is 12 MPa, and the treatment time is 25 min.
[0123] The porous carbonized material is prepared by a method for preparing a porous carbonized biomass material in this embodiment.
[0124] Example 4
[0125] The method for preparing the biomass porous carbonized material comprises the following steps:
[0126] Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed;
[0127] Step 2: Then, the first level of gradient heat treatment is performed. The specific method is: the temperature is first raised to 310°C, kept at this temperature for 6 minutes, and then cooled to room temperature by water cooling;
[0128] Step 3: Place in 4 times the modified circulating stabilizer and stir for modification treatment, the stirring temperature is 42°C, the stirring time is 22min, the stirring speed is 310r / min, after the stirring is completed, wash with water and dry;
[0129] Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment;
[0130] The specific method is: the temperature is first raised to 52°C at a rate of 2°C / s, kept at this temperature for 2 minutes, then raised to 82°C at a rate of 3°C / s, kept at this temperature for 3 minutes, and then air-cooled to room temperature;
[0131] Step 5: Finally, hot pressing is performed to obtain the porous carbonized material of the present invention.
[0132] The biomass carbon in this embodiment is obtained by carbonizing rice husk in a carbonization furnace at a carbonization temperature of 660° C. for 3 hours.
[0133] The method of ball milling improvement treatment in this embodiment is:
[0134] S01: pre-modify the bentonite, and then set it aside after the modification is completed;
[0135] S02: Add the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, then add 3% chitosan and 2% carboxymethyl cellulose based on the total amount of bentonite, stir evenly, and obtain a pre-modified bentonite composite conditioner;
[0136] S03: placing the flaky talc powder in a 4-fold hydrochloric acid solution and stirring and dispersing the solution, stirring the solution evenly to obtain a flaky talc powder;
[0137] S04: S03 flaky talc is added to 4 times the pre-modified bentonite composite conditioner and stirred for reaction. After stirring, the mixture is washed with water and dried to obtain a bentonite composite ball mill;
[0138] S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, the mixture is ready.
[0139] The steps of the pre-modification treatment in this embodiment are: first react at a temperature of 360° C. for 1.2 hours, and then cool to room temperature at a rate of 3° C. / min.
[0140] The mass fraction of the lanthanum sulfate solution in this embodiment is 12%, and the mass fraction of the hydrochloric acid solution is 3%.
[0141] The temperature of the S04 stirring reaction in this embodiment is 47° C., the stirring time is 26 min, and the stirring speed is 600 r / min.
[0142] In S05 of this embodiment, the ball milling speed is 1290 r / min and the ball milling time is 22 min.
[0143] The modified circulation stabilizer of this embodiment includes the following raw materials in parts by weight:
[0144] 3 parts of nickel nitrate, 12 parts of deionized water, 2 parts of resorcinol, and 0.3 parts of silane coupling agent KH560.
[0145] The pressure of the hot pressing treatment in this embodiment is 12 MPa, and the treatment time is 22 min.
[0146] The porous carbonized material is prepared by a method for preparing a porous carbonized biomass material in this embodiment.
[0147] Comparative Example 1
[0148] The difference from Example 3 is that the ball milling improvement treatment is not adopted.
[0149] Comparative Example 2
[0150] The difference from Example 3 is that the ball milling improvement process does not use flaky talc.
[0151] Comparative Example 3
[0152] The difference from Example 3 is that the pre-modified bentonite composite conditioner in the ball milling improvement treatment is directly replaced by bentonite raw material.
[0153] Comparative Example 4
[0154] The difference from Example 3 is that chitosan is not added in the preparation of the pre-modified bentonite composite conditioner.
[0155] Comparative Example 5
[0156] The difference from Example 3 is that lanthanum sulfate is not added in the preparation of the pre-modified bentonite composite conditioner.
[0157] Comparative Example 6
[0158] The difference from Example 3 is that no modified circulating stabilizer treatment is used.
[0159] Comparative Example 7
[0160] The difference from Example 3 is that the second stage gradient heat treatment is not adopted.
[0161] Comparative Example 8
[0162] The difference from Example 3 is that the first stage gradient heat treatment is not adopted.
[0163] The present invention conducts wastewater adsorption experiments on the products of Examples 1-4:
[0164]
[0165] From the product performance tests of Examples 1-4, it can be seen that the product has excellent wastewater adsorption effect and significant adsorption performance;
[0166] The present invention further explores its cycle performance:
[0167] The performance of the products of Examples 1-4 and Comparative Examples 1-8 after 100 cycles with an initial discharge capacity of 2550 mAh / g was tested, and the performance of the products after being placed in 2% hydrochloric acid for 10 hours was also tested;
[0168] It can be seen from Comparative Examples 1-8 and Examples 1-3 that the product of Example 3 has an excellent 100-time discharge capacity, and the product has stable performance under acid corrosion conditions;
[0169] Without ball milling improvement treatment, the acid corrosion performance stability of the product deteriorated significantly. In addition, when the ball milling improvement treatment did not use flaky talcum powder, the pre-modified bentonite composite conditioner in the ball milling improvement treatment was directly replaced by bentonite raw materials, and chitosan was not added in the preparation of the pre-modified bentonite composite conditioner, the performance of the product showed a trend of deterioration. Only the product prepared by the method of the present invention had the most significant performance stability. In addition, without the modified circulating stabilizer treatment, the performance of the product deteriorated significantly. The use of the modified circulating stabilizer can be coordinated with the ball milling improvement treatment, and the two synergistically enhance the performance stability of the product.
[0170] By using the first and second stage gradient heat treatment in conjunction with other product processes, the performance of the product is further optimized and improved.
[0171] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0172] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a porous biomass carbonized material, characterized in that: The following steps are involved: Step 1: Place the biomass carbon in a ball mill for ball milling and then dry it after the ball milling is completed; Step 2: subjecting the product of step 1 to a gradient heat treatment, the specific method being: first raising the temperature to 300-350°C, keeping the temperature for 5-10 minutes, and then cooling to room temperature with water; Step 3: Place the product of step 2 in 3-5 times the modified cycle stabilizer and stir for modification treatment, the stirring temperature is 40-50°C, the stirring time is 20-30min, the stirring speed is 300-400r / min, after the stirring is completed, wash with water and dry; Step 4: subjecting the product of step 3 to a second-stage gradient heat treatment; The specific method is: first increase the temperature to 50-60°C at a rate of 1-3°C / s, keep warm for 1-5 minutes, then increase the temperature to 80-90°C at a rate of 2-5°C / s, keep warm for 2-5 minutes, and then air cool to room temperature; Step 5: subjecting the product of step 4 to hot pressing to obtain the biomass porous carbonized material; Wherein, the method for improving the ball milling process is: S01: pre-modify the bentonite, and then set it aside after the modification is completed; S02: adding the S01 product to the lanthanum sulfate solution at a weight ratio of 1:4, and then adding 2-5% chitosan and 1-3% carboxymethyl cellulose based on the total amount of bentonite, stirring evenly to obtain a pre-modified bentonite composite conditioner; S03: placing the flaky talc in a 3-5 times hydrochloric acid solution and stirring to disperse the flaky talc, stirring evenly to obtain a flaky talc agent; S04: Add S03 flaky talc powder to 3-5 times of pre-modified bentonite composite conditioner and stir for reaction. After stirring, wash with water and dry to obtain bentonite composite ball mill; S05: Bentonite composite ball milling agent and biomass carbon are mixed in a weight ratio of 1:10, and sent into a ball mill for ball milling. When the ball milling is completed, it is done; The steps of the pre-modification treatment are: first react at a temperature of 350-400°C for 1-2h, and then cool to room temperature at a rate of 2-5°C / min; The mass fraction of the lanthanum sulfate solution is 10-20%, and the mass fraction of the hydrochloric acid solution is 2-5%; The temperature of the SO4 stirring reaction is 45-55°C, the stirring time is 20-30min, and the stirring speed is 550-750r / min; The modified circulation stabilizer comprises the following raw materials in parts by weight: 2-5 parts of nickel nitrate, 10-20 parts of deionized water, 1-4 parts of resorcinol, and 0.2-0.6 parts of silane coupling agent KH560.
2. The method for preparing a porous biomass carbonized material according to claim 1, characterized in that: The biomass carbon can be obtained by carbonizing rice husks in a carbonization furnace at a carbonization temperature of 650-700° C. for a carbonization time of 2-4 hours.
3. The method for preparing a porous biomass carbonized material according to claim 1, characterized in that: In the S05, the ball milling speed is 1000-1500 r / min, and the ball milling time is 20-30 min.
4. The method for preparing a porous biomass carbonized material according to claim 1, characterized in that: The pressure of the hot pressing treatment is 10-15 MPa, and the treatment time is 20-30 min.
5. A porous carbonized biomass material prepared by the method for preparing a porous carbonized biomass material according to any one of claims 1 to 4.
